1999
DOI: 10.1038/sj.onc.1202923
|View full text |Cite
|
Sign up to set email alerts
|

Control of E2F activity by p21Waf1/Cip1

Abstract: Cyclin-dependent kinase inhibitors (cdkis), such as p21, are believed to control proliferation through an ability to function as stoichiometric antagonists of cyclin-dependent kinases (cdks). The p21 gene is a direct transcriptional target for the p53 protein, and its activation is likely to be important in e ecting the p53 response. It is widely accepted that p21 can in¯uence cell cycle progression by controlling the activity of cdks that act on the retinoblastoma tumour suppressor protein (pRb) which, in a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
87
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 55 publications
7
87
0
1
Order By: Relevance
“…Our data suggest that E2F-1 may have a similar ability to induce p21 under certain circumstances and is in agreement with a recent study where E2F-1 was found to transactivate p21 (Hiyama et al, 1998). Although one study reported that p21 growth arrest fails to protect gliomal cells from E2F-1-mediated apoptosis (GomezManzano et al, 1999), a growing body of evidence now points to an opposing relationship between E2F-1 and p21 in both cell cycle control and induction of apoptosis (Chen et al, 1995;Shiyanov et al, 1996;Dimri et al, 1996;Hiyama et al, 1998;Delavaine and La Thangue, 1999). In the HT-29 cells, E2F-1-induced p21 did not prevent E2F-1-mediated apoptosis when expressed in the absence of wild-type p53.…”
Section: Discussionsupporting
confidence: 86%
“…Our data suggest that E2F-1 may have a similar ability to induce p21 under certain circumstances and is in agreement with a recent study where E2F-1 was found to transactivate p21 (Hiyama et al, 1998). Although one study reported that p21 growth arrest fails to protect gliomal cells from E2F-1-mediated apoptosis (GomezManzano et al, 1999), a growing body of evidence now points to an opposing relationship between E2F-1 and p21 in both cell cycle control and induction of apoptosis (Chen et al, 1995;Shiyanov et al, 1996;Dimri et al, 1996;Hiyama et al, 1998;Delavaine and La Thangue, 1999). In the HT-29 cells, E2F-1-induced p21 did not prevent E2F-1-mediated apoptosis when expressed in the absence of wild-type p53.…”
Section: Discussionsupporting
confidence: 86%
“…As a cell-cycle inhibitor, p21 plays a critical role in the control of cell growth, but it also plays a role in monocyte differentiation and survival (36)(37)(38). p21 influences cell-cycle progression through cyclin/CDK inhibition, binding to PCNA, and control of E2F transcription and activity (39,40). Although p21 is not a transcription factor, it may exert indirect effects on cellular gene expression.…”
Section: Significancementioning
confidence: 99%
“…In the myeloid lineage, this may be related to direct protein ± protein interactions of p21 with C/EBPalpha (Harris et al, 2001) and with Stat 3 (Coqueret and Gascan, 2000), both of which are required for granulocytic di erentiation (McLemore et al, 2001;Wang et al, 1999). p21 also binds to the p300 transcriptional adapter and alters its activity (Coqueret and Gascan, 2000;Snowden et al, 2000) ; in addition, p21 binds directly to E2F and downmodulates E2F-1 dependent transcription (Delavaine and La Thangue, 1999); Genetic analysis suggests that this could be highly pertinent to di erentiation control (Muller et al, 2001). Hox genes are highly directive of di erentiation and may be among transcriptional targets modulated by p21-complexes .…”
Section: Involvement Of P21 In Differentiationmentioning
confidence: 99%